Helmet towards SIRIM safety mark qualifications / Zulkefli Yusoff - Yusoff, Zulkefli (Faculty of Mechanical Engineering, 2003)
This project work report the mean of testing helmet process to get the Malaysia Standard (MS) for the safety consumer product. The Malaysia standard or the mark will be give to the helmet after they are passing through a several tests, to make sure that the helmet is really safe to use by the consumer before the helmet can be sell in the market. The test is being conducted by SIRIM QAS